Celluloid Pueblo : Western Ways Films and the Invention of the Postwar Southwest - Jenkins, Jennifer L. (Book collections on Project MUSE., 2016)
Celluloid Pueblo tells the story of Western Ways Features and its role in the invention of the Southwest. Founded by Charles and Lucile Herbert in 1936, the Western Ways Features film service documented the landscape, regional development, and diverse cultures of Arizona, the Southwest, and northern Mexico for thirty years. Active during a period of profound growth and transformation, the Herberts created a dynamic visual record of the region; their archival films now serve as a time capsule of the Sunbelt in the mid-20th century. Chapters examine the Herberts' work on the first sound films in the Borderlands, Western Ways' subsequent rise to prominence in the promotion of the Southwest, and the filmic representation of Native and Mexican lifeways, Anglo ranching and leisure, Mexican missions and tourism, and the Borderlands postwar prosperity and progressivism. The story of Western Ways closely follows the boom and bust arc of the midcentury Southwest and its constantly evolving representations of an exotic but safe and domesticated frontier.